Randomized Trial of Left Bundle Branch vs Biventricular Pacing for Cardiac Resynchronization Therapy - Wang, Yao; Zhu, Haojie; Hou, Xiaofeng; Wang, Zhao; Zou, Fengwei; Qian, Zhiyong; Wei, Yongyue; Wang, Xiang; Zhang, Longyao; Li, Xiaofei; Liu, Zhimin; Xue, Siyuan; et al. (Journal of the American College of Cardiology, 2022)
Left bundle branch pacing (LBBP) is the most rapidly growing conduction system pacing technique that is capable of correcting intrinsic left bundle branch block (LBBB). As such, it is potentially an optimal alternative to cardiac resynchronization therapy (CRT) with biventricular pacing (BiVP). The authors sought to compare the efficacy of LBBP-CRT with BiVP-CRT in patients with heart failure and reduced left ventricular ejection fraction (LVEF). This is a prospective, randomized trial of patients with nonischemic cardiomyopathy and LBBB with 6-month preplanned follow-up. Crossovers were allowed if LBBP or BiVP were unsuccessful. The primary endpoint was the difference in LVEF improvement between 2 groups. The secondary endpoints included changes in echocardiographic measurements, N-terminal pro–B-type natriuretic peptide (NT-proBNP), New York Heart Association functional class, 6-minute walk distance, QRS duration, and CRT response. The study included 40 consecutive patients (20 males, mean age 63.7 years, LVEF 29.7% ± 5.6%). Crossovers occurred in 10% of LBBP-CRT and 20% of BiVP-CRT. All patients completed follow-up. Intention-to-treat analysis showed significantly higher LVEF improvement at 6 months after LBBP-CRT than BiVP-CRT (mean difference: 5.6%; 95% CI: 0.3-10.9; P = 0.039). LBBP-CRT also appeared to have greater reductions in left ventricular end-systolic volume (−24.97 mL; 95% CI: −49.58 to −0.36 mL) and NT-proBNP (−1,071.80 pg/mL; 95% CI: −2,099.40 to −44.20 pg/mL), and comparable changes in New York Heart Association functional class, 6-minute walk distance, QRS duration, and rates of CRT response compared with BiVP-CRT. LBBP-CRT demonstrated greater LVEF improvement than BiVP-CRT in heart failure patients with nonischemic cardiomyopathy and LBBB. (Left Bundle Branch Pacing Versus Biventricular Pacing for Cardiac Resynchronization Therapy [LBBP-RESYNC]; NCT04110431) [Display omitted]